Thermal Influence of an Alpine Deep Hydrothermal Fault on the Surrounding Rocks. Issue 1 (2nd January 2015) - Dzikowski, Marc; Josnin, Jean Yves; Roche, Nicolas
Abstract: Major fault zones in mountain areas are often associated with cold‐water circulations and hydrothermal pathways. Compared with the massif as a whole, the deep groundwater flows in these high hydraulic‐conductivity zones modify the thermal state of the surrounding rock. This paper examines the thermal effects of groundwater flow in the area around the steeply dipping La Léchère deep fault zone (LFZ, French Alps) and associated shallow decompressed zone. We used a 3D numerical model drawn up from groundwater circulation data to investigate the La Léchère hydrothermal system and the thermal state of the rock in the valley sides. Hydrothermal simulations showed that convective flow into the LFZ cools the valley sides and creates a thermal upwelling under the valley floor. An unsteady thermal regime that continues for about 10, 000 years is also needed to obtain the temperatures currently found under the valley floor in the LFZ. Temperature‐depth profiles around the LFZ show disturbances in the thermal gradients in the valley sides and the valley floor. Convective heat transfer into the LFZ and the decompressed zone, and conductive heat transfer in the surrounding rocks produce an unsteady, asymmetric thermal state in the rock on both sides of the LFZ.